The effectiveness of media communication and its problems in the contemporary theatrical presentation (Al-Academy, 2021)
The theater can be considered a media that the effectiveness of its tools and the perceptions it produces cannot be abandoned according to patterns or aesthetic artistic trends, and at the same time it carries a large amount of information that can be worked on activating it with conscious directions within the elements of the theatrical performance, and these can be counted The study is an attempt to trace the functioning of the communication and media elements in the structure of the theatrical performance, as the study included: An introduction that defines the research problem and its importance, which crystallized around the following question: Does the media communication through theatrical presentation form its desired effectiveness in developing awareness towards realizing the facts of its audience? The research is based on two theoretical topics, namely the first topic (Communication Effectiveness, principles and references), which includes the philosophical and procedural references to the concept of communication and the media, while the second topic deals with (theatrical presentation is a means of media communication) in which the work of international directors in activating the elements of communication and media in their theatrical performances was presented. . In the research procedures, an intentional sample was chosen for the purpose of analysis represented in the play (curfew) that was shown in Baghdad in 2006, and the descriptive analysis was based on according to the research indicators that came out of the theoretical framework, leading to the results, including: 1- The effectiveness of media communication in Theatrical performance as it is intertwined with the artistic and aesthetic discourse 2- The effectiveness of media communication in theatrical presentation varies according to the different types of performances and their theatrical directions. Some of them are direct speeches, and some are implicit speeches.Finally, a list of research references and a summary in English